Education on Prevention and Control of Hypertension and Diabetes Mellitus for Pattients at Primary Health Care Center at Primary Healtj Center: A Community Service Program - Putri, Elsa Mahardika; Okky Intan Mawarni; Winartiana; Maharani Dwi Pratiwi; Evi Nurul Hiadayati (Journal of Community Engagement in Health, 2025)
Hypertension and diabetes mellitus are major non-communicable diseases (NCDs) that pose a serious health burden, particularly among the elderly. This community service activity aimed to increase knowledge and awareness regarding prevention and control of these diseases among outpatients at the Bandung Community Health Centre, Tulungagung Regency. The activity was conducted on July 11, 2025, involving 40 participants selected based on SIMPUSTA records indicating a history or risk of hypertension and diabetes mellitus. Participants hypertension and random blood glucose checks before receiving direct health education. The educational session was delivered using verbal explanations and leaflets, focusing on symptoms, complications, and disease management. Results showed that 15% of participants had hypertension and 30% had uncontrolled blood sugar. These findings align with national trends and highlight the importance of regular screening and targeted education. This program demonstrated that simple interventions in primary care settings can effectively promote early detection and Improve chronic disease management, especially when supported by interactive and community-based health promotion strategies. However, this program did not include quantitative evaluation of the educational intervention, which limits the ability to measure its direct impact on participants knowledge and behavior.